Pengaruh Penggunaan Padlet pada Pembelajaran Bahasa Inggris: Sebuah Studi Komparatif - Heri Retnawati; Alfelia Nugky Permatasari; Hasan Djidu (DBSMB, Vocational College of Universitas Gadjah Mada, 2022)
The existence of information and communication technology, especially the internet, offers great opportunities for language teachers and learners to maximize their learning experience. The role of the internet is increasingly significant as a solution to the limited class activities that are usually carried out to realize collaborative learning during the pandemic. In fact, this learning practice is considered to be able to improve student learning performance. One of the media that can be used by utilizing the internet in collaborative learning practices is Padlet. This comparative study on two different English courses, English Grammar for Corporate Documents (EGCD) and General Reading, aims to prove whether Padlet can help English learners improve their learning performance. The score of 60 students of the Applied English Undergraduate Study Program in both courses before and after using the Padlet during the learning process was used as data. After testing the normality and homogeneity of the data, the MANOVA test was used to test the research hypothesis. The data were analyzed using IBM SPSS Statistics software (version 26) and then interpreted and used to draw conclusions. The results showed that there was a positive influence given by Padlet use on the language learning process seen from the average value of the learners in both courses. However, a significant effect is only shown by the EGCD course.